Psychosocial and physical risk factors of mental health among laboratory workers in a Malaysian public university - Md Saad, Zuliza (2017)
Mental health problems is a broad range disorders that lead to serious illness as a long-term effects if not addressed immediately. The aim of this study was to determine the prevalence and associated factors related to Probable Mental Health Problems of UPM laboratory workers. A cross-sectional study was carried out from January 2014 to June 2015. The workers were asked to complete a set of questionnaires, including background information, Job Content Questionnaire (JCQ-27), Sick Building Syndrome (SBS) and General Health Questionnaire (GHQ-12). 264 laboratory workers completed the questionnaire. The prevalence of Probable Mental Health Problems of respondents was 28% and the prevalence of Sick Building Syndrome was 31.4%. At dry laboratories, mean temperature was significantly higher than wet laboratories (p<0.032). Higher temperature was significantly associated with higher GHQ scores (p<0.017). At wet laboratories, mean concentration of carbon monoxide was significantly higher than dry laboratories (p<0.002). Lower temperature (p< 0.015) and lower relative humidity (p< 0.047) were significantly associated with higher GHQ scores. The most frequent SBS was drowsiness (12.1%) followed by irritating and runny nose (8.3%), fatigue (7.6%) and headache (5.7%). Based on final model of multivariate analyses job insecurity (AOR 2.33; 95%CI 0.212- 0.867), high job demand (AOR 1.12; 95%CI 0.445-0.921), fatigue (AOR 0.94; 95%CI 0.162-1.425), drowsiness (AOR 0.75; 95%CI 1.023-4.647) and household income (AOR 0.34; 95%CI 0.166-0.995) were predictors of Probable Mental Health Problems among the respondents. In conclusion, there were associations between sociodemographic, psychosocial factors and SBS with mental health status among UPM laboratory workers. Hence, further assessment should be carried out to reduce the risk factors that occur in laboratory working environment.